Perilaku Cyberbullying Pada Emerging Adulthood: Peran Kontrol Diri dan Regulasi Emosi - Siti Marwah; Rahayu Utami Rahman, Puspa; Yuwono Pratomo, R. (IDEA: Jurnal Psikologi, 2024)
Technological advancements have significantly impacted their users, including negative effects such as cyberbullying. According to a survey by the Association of Internet Service Providers in Indonesia (APJII), internet users are predominantly from the early adulthood age group, with West Java ranking second in highest internet penetration among the Indonesian islands. This study aims to determine whether self-control and emotion regulation influence cyberbullying behavior among emerging adults in West Java. The research employs a quantitative method with a causal design. The study includes 385 respondents selected through convenience sampling. Researchers utilized three standardized scales: the Brief Self-Control Scale (BSCS), Emotion Regulation Questionnaire (ERQ), and Cyberbullying Perpetration (CBP). Data analysis was conducted using multiple regression analysis (T-test and F-test) with SPSS version 25.0 for Windows. The research findings show a significance value of 0.000 (p < 0.05), indicating that self-control and emotion regulation have a significant influence on cyberbullying behavior. Based on these results, it can be concluded that the alternative hypothesis (Ha) is accepted while the null hypothesis (H0) is rejected, meaning that self-control and emotion regulation indeed influence cyberbullying behavior among emerging adults in West Java, contributing 18.5% to the variance. Individuals in emerging adulthood are encouraged to strengthen their self-control and emotion regulation to reduce cyberbullying behavior, thereby creating a healthier and safer online environment.